Pool of endoglucanase genes in Schizophyllum commune Fr.:Fr. (Basidiomycetes) on the territory of Ukraine - Boiko, Sergiy M. (Acta Biologica Szegediensis, 2018)
Pool of intracellular endoglucanases of the fungus Schizophyllum commune on the territory of Ukraine was studied. Two loci of endoglucanase (Eg1, Eg2) were found. The polymorphic locus Eg2 controls the expression of four alleles. Alleles Eg293, Eg296 and Eg2102 are rare and peculiar to certain populations. Amino acid sequence of the locus Eg2 in databases of NCBI (XP_003031634.1) and UniProt (D8Q439) was probably identified. It is classified among the family 5 (GH5) and consists of 333 amino acid residues.